A Glass Half Full : The Promise of Regional Trade in South Asia - Kathuria, Sanjay (Washington, DC: World Bank, 2018)
Trade has played a critical role in global poverty reduction. In harnessing the potential of trade, some of the most successful countries have developed strong trade relationships with their neighbors. However, many South Asian countries have trade regimes that often offset the positive impact of geography and proximity.